PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DI PT. TRUSTLOG TOTAL SOLUSINDO - Wahjudi Utomo Mahdjub; Pompong Budi Setiadi; Sri Rahayu (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The implication of the right organizational culture, supported by a good work environment and the right leadership style in its function of managing human resources in a company will have an impact on the work behavior of employees in a company which will ultimately affect the performance of a company as a whole. The purpose of this study was to determine the effect of work environment organizational culture and leadership style on employees at PT Trustlog Total Solusindo in Surabaya. The instrument of this research used a questionnaire. Samples were taken as many as 40 respondents employees of PT Trustlog Total Solusindo in the city of Surabaya. Analysis and data processing using SPSS. The results of this study indicate that organizational culture and leadership style have no effect on employee performance, while the work environment affects employee performance